Factors linked to poor self-rated health in thyroid disorder patients: findings from LASI Wave-I - Pawan Kumar; Arunima Sen; Priyanshu Priyanshu; Mahalaqua Nazli Khatib; R. Roopashree; Mandeep Kaur; Manish Srivastava; Amit Barwal; G. V. Siva Prasad; Pranchal Rajput; Muhammed Shabil; Rukshar Syed; et al. (Thyroid Research)
Abstract Background Thyroid disorders affect the physical, behavioural, and psychological aspects of an individual, leading to poor self-rated health (SRH). Hence, we aimed to determine the prevalence of poor SRH and the factors associated with it among thyroid disorder patients. Methods This is an observational study consisting of 2336 thyroid disorder patients from LASI, 2017-19. Descriptive statistics were employed to calculate prevalence. The association between poor SRH and socio-demographic variables was evaluated using regression analysis, with results expressed as (AOR) and 95% CI. Results The findings showed poor self-rated health predictors among thyroid disorder patients, where 25% rated their health as poor. Significant predictors included older age, with patients aged ≥ 75 years having a higher likelihood of reporting poor health (aOR = 2.36, 95% CI = 1.32–4.22, p = 0.004), and rural residence (aOR = 1.34, 95% CI = 1.07–1.67, p = 0.011). Belonging to the OBC caste (aOR = 1.57, 95% CI = 1.23–2.00, p < 0.001) and practicing Christianity (aOR = 1.90, 95% CI = 1.25–2.89, p = 0.003) were also associated with increased odds of poor SRH. Previous employment (aOR = 1.65, 95% CI = 1.20–2.25, p = 0.002), co-morbidities (aOR = 2.59, 95% CI = 1.88–3.59, p < 0.001), and lower education levels (aOR = 1.50, 95% CI = 1.06–2.13, p = 0.022) were significant. Limitations in activities of daily living and instrumental activities of daily living were linked to poorer health outcomes (aOR = 1.76, 95% CI = 1.33–2.31, p < 0.001; IADL: aOR = 1.41, 95% CI = 1.11–1.79, p = 0.004). Depression (aOR = 1.84, 95% CI = 1.32–2.56, p < 0.001) and healthcare utilization in the past year (aOR = 1.86, 95% CI = 1.33–2.58, p < 0.001) also predicted poor SRH, with most healthcare utilization (79.8%) occurring in private facilities. Conclusion The study highlights a high prevalence of poor SRH among patients, with significant associations observed with age, residence, comorbidity, and healthcare utilization. Targeted interventions focusing on healthcare access, physical activity, and mental health support are crucial to improve SRH.